Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/mas.21511
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase basicities of polyfunctional molecules. Part 5: Non‐aromatic sp2 nitrogen containing compounds

Abstract: This paper constitutes the fifth part of a general review of the gas-phase protonation thermochemistry of polyfunctional molecules (Part 1: Theory and methods, Mass Spectrom Rev 2007, 26:775-835, Part 2: Saturated basic sites, Mass Spectrom Rev 2012, 31:353-390, Part 3: Amino acids, Mass Spectrom Rev 2012, 31:391-435, Part 4: Carbonyl as basic site, Mass Spectrom Rev 2015, 34:493-534). This part is devoted to non-aromatic molecules characterized by a lone pair located on a sp nitrogen atom, it embraces functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 118 publications
(239 reference statements)
1
19
0
Order By: Relevance
“…This choice does not imply a priori that the The cyclopropenimine (or cyclopropeneimine, less common name) skeleton (Z: N) has a special status among the heteroatomic analogs of methylenecyclopropene. It is present in many systems, which have been largely studied experimentally and theoretically, in particular in the last ten years, as platforms for developing superbases and organocatalysts [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The imino bond carrying a nitrile group on the nitrogen, >C=N−CN, is present in molecules of biological interest, in particular the neonicotinoids [35][36][37], and in materials developed for their electronic applications [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…This choice does not imply a priori that the The cyclopropenimine (or cyclopropeneimine, less common name) skeleton (Z: N) has a special status among the heteroatomic analogs of methylenecyclopropene. It is present in many systems, which have been largely studied experimentally and theoretically, in particular in the last ten years, as platforms for developing superbases and organocatalysts [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The imino bond carrying a nitrile group on the nitrogen, >C=N−CN, is present in molecules of biological interest, in particular the neonicotinoids [35][36][37], and in materials developed for their electronic applications [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The third part is a survey of the present knowledge on the experimental and theoretical gas‐phase protonation thermochemistry of the 20 gaseous proteinogenic aminoacids. The fourth part was devoted to polyfunctional molecules bearing a carbonyl group as basic site and finale the fifth part is focused on the basicity properties of non aromatic molecules characterized by a lone pair located on a sp 2 nitrogen atom (ie, imines, amidines, guanidines, diazenes, hydrazines, oximes, and phosphazenes) . The present part is concerned with molecules containing sp hybridized nitrogen atoms, that is cyanides (nitriles) and isocyanides (isonitriles).…”
Section: Introductionmentioning
confidence: 99%
“…A number of molecules studied here include species characterized by large proton affinity and gas‐phase basicity values, due, in particular to the so‐called “push‐pull effect” where a π‐donnor subtituent is directly linked to the nitrile group . Accordingly, some of these molecules are denoted as “superbases,” that is are stronger bases than the classical proton sponge, 1,8‐bis(dimethylamino)naphthalene (see parts 2 and 5 of this review), which is characterized by a proton affinity (PA) of 1015 kJ/mol, and a gas‐phase basicity (GB) of 980 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…Most GB values for nitrogen compounds are available in the literature [50,51] but not for the targeted pesticides. It was observed that gas phase basicity increases from nitriles < amines < amides < pyroles < pyrimidines < pyridines.…”
Section: So What Happens During Hot Splitless Injection To Suppress Tmentioning
confidence: 99%